Environmental firms' better attitude towards nature in the context of corporate compliance - Robina Ramírez, Rafael; Palos-Sánchez, Pedro R (Sustainability, 2019)
The recent publishing of the Criminal Code Reform, known as the Corporate Governance Code and by which companies are prosecuted for the crimes they have committed, is contributing towards improving the management of companies involved in using natural resources. This study explores the disposition of environmental companies towards respect for nature in the context of the new Spanish Criminal Code 1/2015. Over 916 companies, including 104 environmental companies, have been asked about their knowledge of the code and the consequences it has for them through a survey. The paper explores the influence of regulatory compliance, coercive enforcement and cooperative actions on environmental companies to develop better attitudes towards nature. Partial Least Squares (PLS) Path Modelling was used to build an interaction model among variables. The results of the research reveal how environmental companies are more inclined to developing organizational standards (Cooperative Environmental Protocols) and to improving compliance with environmental law (coercive regulation). The model has a moderate predictive effect, explaining 54.1% of environmental companies' Better Attitude towards Nature. The findings may have important implications for environmental authorities when deterring environmental crimes.
Keywords: environmental companies; nature; coercive regulation; corporate compliance; organizational standards; surveillance; cooperative regulation; environmental crime; Spanish Criminal Code; PLS-SEM; JCR; Scopus